Upaya Peningkatan Capaian Pemberian ASI Eksklusif (Pendekatan Social Cognitive) - Martha Ariana Wijayanti; Binti Maratus Sholikhah; Ernawaty Ernawaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to identify the effect of self-efficacy, outcome expectations, socio-structural factors, and intention on the behavior of the infant-mother (6-24 months) in exclusive breastfeeding. The research design used was observational with a cross-sectional approach. This study indicates that the variables that affect the mother's intention to provide exclusive breastfeeding are socio-structural factors (p = 0.016). Respondents who choose to provide exclusive breastfeeding will have the behavior of giving exclusive breastfeeding (p = 0.003). In contrast, self-efficacy (p = 0.340) and outcome expectations (p = 0.682) do not affect the mother's intention. Likewise, the mother's exclusive breastfeeding behavior was not influenced by self-efficacy (p = 0.294) and outcome expectations (p = 0.586). In conclusion, the factors that influence a mother's exclusive breastfeeding behavior are intention and socistructural factors. Keywords: Exclusive breastfeeding, Cognitive Social Approach